Biomodification Strategies for the Development of Antimicrobial Urinary Catheters: Overview and Advances. Issue 1 (27th December 2017) - Anjum, Sadiya; Singh, Surabhi; Benedicte, Lepoittevin; Roger, Philippe; Panigrahi, Manoj; Gupta, Bhuvanesh
Abstract: Microbial burden associated with medical devices poses serious health challenges and is accountable for an increased number of deaths leading to enormous medical costs. Catheter‐associated urinary tract infections are the most common hospital‐acquired infections with enhanced patient morbidity. Quite often, catheter‐associated bacteriuria produces apparent adverse outcomes such as urosepsis and even death. Taking this into account, the methods to modify urinary catheters to control microbial infections with relevance to clinical drug resistance are systematically evaluated in this review. Technologies to restrict biofilm formation at initial stages by using functional nanomaterials are elucidated. The conventional methodology of using single therapeutic intervention for developing an antimicrobial catheter lacks clinically meaningful benefit. Therefore, catheter modification using naturally derived antimicrobials such as essential oils, curcumin, enzymes, and antimicrobial peptides in combination with synthetic antibiotics/nanoantibiotics is likely to exert sufficient inhibitory effect on uropathogens and is extensively discussed. Futuristic efforts in this area are projected here that demand clinical studies to address areas of uncertainty to avoid development of bacterial resistance to the new generation therapy with minimum discomfort to the patients. Abstract : In this review, the modification of urinary catheters for infection control that can serve as the gateway to a new face of the future in the field of human healthcare is discussed. The innovation is related to the discussion of novel strategies for catheter functionalization with use of several synthetic and natural antimicrobial agents including biopolymeric hydrogels and herbal nanoantibiotics.